DUKUNGAN SOSIAL DAN HARDINESS TERHADAP STRES AKADEMIK PADA SISWA SEKOLAH PENGGERAK (KURIKULUM MERDEKA) - Fadhilah, Alifah Qisthi; Purwantini, Lucky; Hanoum, Magdalena (SOUL : Jurnal Pemikiran dan Penelitian Psikologi, 2024)
There are various forms of education in Indonesia, and highschool education is one of them. High school studentsbelong to the adolescent age group characterized bycuriosity for new experiences, and unresolved curiosity canlead to academic stress. This study aims to examine therelationship between social support, hardiness, andacademic stress among Sekolah Penggerak students usingindependent curriculum. The study sample consisted of 199students from grade 1 selected through cluster randomsampling. The data collection methods of the study wereinterviews and psychological scales. The research used theEducational Stress Scale for Adolescents (ESSA),Multidimensional Scale of Perceived Social Support(MSPSS), and the Hardiness Scale. For the analysis,correlation and multiple regression tests were used.Correlation test results showed a significant relationshipbetween social support and academic stress (r=-0,428,p<0,001) and hardiness and academic stress (r=-0,396,p<0,001). Social support and hardiness explained 26.2% ofacademic stress (R2=0.262; F(2,196)=36.237, p<0.001).